Profile of plastic surgeons in the state of Goias, Brazil - Fabiano Calixto Fortes de Arruda; Paulo Renato de Paula; Celmo Celeno Porto (Revista Brasileira de Cirurgia Plástica, 2016)
INTRODUCTION: Plastic surgery has become popular in the recent years for the access to procedures and exposure in the media. The current scenario brings difficulties in the job market because of competitiveness and reduced fees. This study describes the profile of the plastic surgeons working in the state of Goias. METHODS: The survey was conducted with plastic surgeons who work in the state of Goias and are registered in local chapter of the Brazilian Society of Plastic Surgery in January 2015. Data were divided into socio-economic and demographic profile. Inclusion criteria were residence certified by the Brazilian Ministry of Education or by the Brazilian Society of Plastic Surgery,, practice of plastic surgery in the state of Goias. We excluded residents in plastic surgery, and those who not practice in plastic surgery area. RESULTS: Rate of response was 70%. Most participants were younger than 40 years old, men, married, with 1-2 children, work in Goias, had less than 10 years as a surgeion, had specialization in plastic surgery, work 40-60 hours weekly and main practice was in aesthetic and reconstructive area, the majority of them do not employ assistances in more than 50% of surgeries. CONCLUSION: The profile of plastic surgeon in state of Goias is composed by young physicians, men, married, with no more than 2 children, and whom practice mainly in the state capital, most of them are specialists, work 40-60 hours per week, and their main practice is with aesthetic and reconstructive surgery.